Health outcomes in diabetics measured with Minnesota Community Measurement quality metrics - Takahashi, Paul Y (Diabetes Metab Syndr Obes, 2014)
OBJECTIVE: Our objective was to understand the relationship between optimal diabetes control, as defined by Minnesota Community Measurement (MCM), and adverse health outcomes including emergency department (ED) visits, hospitalizations, 30-day rehospitalization, intensive care unit (ICU) stay, and mortality. PATIENTS AND METHODS: In 2009, we conducted a retrospective cohort study of empaneled Employee and Community Health patients with diabetes mellitus. We followed patients from 1 September 2009 until 30 June 2011 for hospitalization and until 5 January 2014 for mortality. Optimal control of diabetes mellitus was defined as achieving the following three measures: low-density lipoprotein (LDL) cholesterol <100 mg/mL, blood pressure <140/90 mmHg, and hemoglobin A(1c) <8%. Using the electronic medical record, we assessed hospitalizations, ED visits, ICU stays, 30-day rehospitalizations, and mortality. The chi-square or Wilcoxon rank-sum tests were used to compare those with and without optimal control. We used Cox proportional hazard models to estimate the associations between optimal diabetes mellitus status and each outcome. RESULTS: We identified 5,731 empaneled patients with diabetes mellitus; 2,842 (49.6%) were in the optimal control category. After adjustment, we observed that non-optimally controlled patients had higher risks for hospitalization (hazard ratio [HR] 1.11; 95% confidence interval [CI] 1.00–1.23), ED visits (HR 1.15; 95% CI 1.06–1.25), and mortality (HR 1.29; 95% CI 1.09–1.53) than diabetic patients with optimal control. No differences were observed in ICU stay or 30-day rehospitalization. CONCLUSION: Diabetic patients without optimal control had higher risks of adverse health outcomes than those with optimal control. Patients with optimal control defined by the MCM were associated with decreased morbidity and mortality.